IDEAS DEVELOPMENT PATTERNS OF ENGLISH EXPOSITORY DISCOURSES BY INDONESIANS AS REFLECTED IN THE JAKARTA POST - Katharina Rustipa (Universitas Stikubank (UNISBANK) Semarang, 2012)
This study investigates the ideas organizational patterns that underlie the writing of English Expository discourses performed by Indonesians. Organizational pattern constitutes one of the features that contribute to text coherence. The data of the study consist of 6 expository discourses taken from The Jakarta Post. The study is descriptive and qualitative in nature. It describes the observed phenomena in the form of words rather than numbers. The characteristics of the organizational patterns underlying the English expository discourses written by Indonesians are identified and analyzed. The results of the study show that fifty percent of the English Expository Discourses written by Indonesians reflects the linear organizational pattern. Some suggestions that can be put forward are as follows: the linear organizational pattern should become the teaching material of composition subject. The students should be reminded that when writing in English, they should follow English rule including in developing ideas. Comparisons between linear and non linear organizational patterns should be presented to the students to make them aware of the differences. Key words: organizational patterns, linear development pattern, circular development pattern, digress development pattern, parallel development pattern